A dual-configuration catalyst for furfural aqueous phase hydrogenation reaction and preparation method thereof

By uniformly distributing metal M on the ZSM-5 zeolite molecular sieve to form a dual-configured catalyst, the problem of low selectivity of existing nickel-based catalysts in furfural hydrogenation reaction is solved, and higher catalytic activity and selectivity are achieved, reducing the generation of by-products.

CN116532150BActive Publication Date: 2025-04-11SOUTHEAST UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310352622.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-04
Publication Date
2025-04-11
Estimated Expiration
2043-04-04

AI Technical Summary

Technical Problem

The existing nickel-based catalysts have low selectivity in furfural hydrogenation reaction, and the single catalyst structure cannot effectively control the hydrogenation reaction path of furfural in the aqueous phase, resulting in an increase in by-products.

Method used

ZSM-5 zeolite molecular sieve is used as a support to uniformly distribute metal M (such as Ni, Cu, Fe or Co) on the inside and surface of the zeolite molecular sieve to form a dual-configured catalyst, shortening the spatial distance between the metal hydrogenation site and the acid site of the zeolite molecular sieve, thereby improving the selectivity and activity of the catalyst.

Benefits of technology

The selectivity and catalytic activity of the aqueous hydrogenation reaction of furfural phase is significantly improved, the generation of by-products is reduced, and the dual-function catalytic synergy of the catalyst is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116532150B_ABST
    Figure CN116532150B_ABST
Patent Text Reader

Abstract

The invention discloses a furfural aqueous phase hydrogenation reaction dual-configuration catalyst and a preparation method thereof. The catalyst carrier is a ZSM-5 zeolite molecular sieve, the carrier zeolite molecular sieve comprises two parts of metal M, one part of the metal M is uniformly dispersed in the zeolite molecular sieve and wrapped by the zeolite molecular sieve, and the other part of the metal M is uniformly loaded on the surface of the zeolite molecular sieve; wherein the metal M is Ni, Cu, Fe or Co; firstly, a hydrothermal coating method is adopted to coat the metal M in the zeolite molecular sieve, and then an in-situ hydrothermal method is adopted to uniformly load the metal M on the surface of the zeolite molecular sieve; the metal M is uniformly distributed in and on the surface of the zeolite molecular sieve, the spatial distance between the metal hydrogenation site and the acid site of the zeolite molecular sieve is shortened, and in the reaction process, the furfuryl alcohol can be effectively prevented from excessively contacting with the acid site to generate humus, and the intermediate product diffused to the surface of the zeolite can be further hydrogenated to form a target product, thereby greatly improving the dual-function catalytic synergistic ability of the catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a catalyst and a preparation method thereof, and in particular to a dual-configuration catalyst for furfural aqueous phase hydrogenation reaction and a preparation method thereof. Background Art

[0002] The energy and environmental problems brought about by the massive consumption of fossil energy need to be solved urgently. In order to achieve sustainable development, renewable energy has been widely studied. Furfural, a lignocellulose derivative, is one of the most widely used biomass platform chemicals. Many high-value derivatives and downstream products can be produced from furfural. Among them, γ-valerolactone is an important chemical intermediate in industry. Due to its vanillin and coconut aroma, it is widely used in the preparation of peach, coconut, vanilla and other flavors. Designing a green and sustainable synthesis route of valerolactone has become a hot topic in current research. Precious metals show good catalytic performance, but their high cost and limited reserves have greatly restricted their industrial application. In recent years, more and more research has focused on non-precious metal catalysts. Nickel-based catalysts show good hydrogenation activity, but the adsorption mode of furfural on the nickel metal surface leads to low selectivity for furfural hydrogenation. At the same time, a single catalyst structure cannot effectively control the hydrogenation reaction path of furfural in the aqueous phase, resulting in an increase in by-products. Summary of the invention

[0003] Purpose of the invention: The present invention aims to provide a dual-configuration catalyst for the aqueous phase hydrogenation reaction of furfural with improved selectivity and catalytic activity; the second purpose of the present invention is to provide a method for preparing the dual-configuration catalyst for the aqueous phase hydrogenation reaction of furfural.

[0004] Technical solution: The dual-configuration catalyst for the aqueous phase hydrogenation reaction of furfural of the present invention has a carrier of ZSM-5 zeolite molecular sieve, and the carrier zeolite molecular sieve includes two parts of metal M, one part of the metal M is uniformly dispersed inside the zeolite molecular sieve and wrapped by the zeolite molecular sieve, and the other part of the metal M is uniformly loaded on the surface of the zeolite molecular sieve; wherein the metal M is Ni, Cu, Fe or Co.

[0005] In the reaction of furfural selectively preparing γ-valerolactone, the reactant furfural needs to be hydrogenated alternately at the metal and acid sites. The above-mentioned dual-configuration catalyst can evenly distribute the metal inside and on the surface of the zeolite molecular sieve, shortening the spatial distance between the metal hydrogenation site and the zeolite molecular sieve acid site. Therefore, during the reaction process, it can effectively prevent furfuryl alcohol from excessively contacting the acid site to form humus, and further hydrogenate the intermediate product diffused to the zeolite surface to form the target product, greatly improving the dual-functional catalytic synergistic ability of the catalyst.

[0006] Preferably, the content of the ZSM-5 zeolite molecular sieve is 60-80wt%, the metal M content dispersed inside the zeolite molecular sieve is 1-20wt%, and the metal M content loaded on the surface of the zeolite molecular sieve is 1-20wt%. The difference in the metal M loading leads to the difference in catalyst performance. As the loading increases, the catalyst provides more metal active sites in the reaction, thereby effectively improving the furfural hydrogenation performance. However, too high a metal M loading can cause the metal to agglomerate, and it is easy to sinter at high temperatures, which seriously affects the furfural hydrogenation performance.

[0007] Preferably, the ZSM-5 zeolite molecular sieve is subjected to Si removal treatment. The Si removal of the zeolite molecular sieve forms a large number of mesopores, which increases the specific surface area of ​​the catalyst and increases the proportion of Al content in the ZSM-5 zeolite, which can effectively provide acid sites.

[0008] The method for preparing the dual-configuration catalyst for furfural aqueous phase hydrogenation reaction of the present invention comprises the following steps:

[0009] (1) preparing a ZSM-5 precursor solution;

[0010] (2) mixing the metal M salt, polyvinyl pyrrolidone and ZSM-5 precursor solution, stirring evenly, and then performing a hydrothermal reaction to obtain a ZSM-5 zeolite molecular sieve coated with metal M M@ZSM-5 composite material;

[0011] (3) Dissolve the metal M salt in the ammonia solution and stir evenly to form a metal M complex ammonia solution [M(NH 3 ) 4 ] 2+ , adding the M@ZSM-5 composite material obtained in step (2), stirring evenly, and performing a hydrothermal reaction to obtain a dual-configuration composite material with layered metal M silicate in situ grown on the surface of M@ZSM-5;

[0012] (4) The product obtained in step (3) is subjected to high temperature roasting and reduction to obtain a furfural aqueous phase hydrogenation conversion dual-configuration catalyst M / M@ZSM-5.

[0013] Preferably, in step (1), the ZSM-5 precursor solution is tetraethyl orthosilicate (TEOS):NaAlO 2 :Tetrapropylammonium hydroxide (TPAOH):H 2 O is mixed in a molar ratio of 1: (0.002-0.04): (0.015-0.3): (10-50).

[0014] In step (2), the M@ZSM-5 composite material is prepared by a hydrothermal coating method. After the zeolite crystals are treated with an alkaline solution, the Si-O-Si bonds are selectively hydrolyzed, the Si species in the framework are preferentially extracted, and the Al species are enriched on the outer surface of the crystals, which acts as a pore directing agent to induce the formation of mesoporous zeolite by selective Si leaching. At this time, the zeolite crystals are coated with metal M. Preferably, in step (2), the hydrothermal reaction conditions are 80 to 200° C. for 5 to 36 hours.

[0015] In step (3), metal M and Si-containing zeolite grow metal silicate in situ under alkaline conditions, which enhances the interaction between the metal M active component and the carrier, so that the metal silicate is evenly distributed on the surface of the zeolite molecular sieve, thereby improving the stability of the catalyst. Preferably, in step (3), in the metal M complex ammonia solution, the [M(NH 3 ) 4 ] 2+ The content of is 0.05-2wt%, the content of ammonia is 5-35wt%, the pH value of the metal complex ammonia solution is 9-12; the hydrothermal reaction conditions are 80-200°C for 10-24h.

[0016] Preferably, in step (4), the calcination condition is calcination at 400-700°C for 3-10h; the reduction condition is reduction at 300-700°C for 1-5h, and the reducing atmosphere is H 2 or H 2 / N 2 Mixed gases.

[0017] Preferably, the metal M salt is metal M nitrate.

[0018] Invention mechanism: In the reaction of furfural selectively preparing γ-valerolactone, the reactant furfural needs to be hydrogenated alternately at the metal and acid sites (such as Figure 1 The dual-configuration catalyst of the present invention can make the metal evenly distributed inside and on the surface of the zeolite molecular sieve, shortening the spatial distance between the metal hydrogenation site and the zeolite molecular sieve acid site. Therefore, during the reaction process, it can effectively prevent furfuryl alcohol from excessively contacting the acid site to form humus, and can further hydrogenate the intermediate product diffused to the zeolite surface to form the target product (such as Figure 2 The bifunctional catalytic synergy of the catalyst was greatly enhanced.

[0019] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The dual-configuration catalyst can make the metal evenly distributed inside and on the surface of the zeolite molecular sieve, shortening the spatial distance between the metal hydrogenation site and the zeolite molecular sieve acid site. During the reaction process, it can effectively prevent furfuryl alcohol from excessively contacting the acid site to generate humus, and further hydrogenate the intermediate product diffused to the zeolite surface to form the target product, greatly improving the dual-functional catalytic synergistic ability of the catalyst; (2) The zeolite molecular sieve is de-Si under alkaline conditions to form a large number of mesopores, which increases the specific surface area of ​​the catalyst and improves the dispersibility of the active component of the catalyst metal M. At the same time, the Al content in the ZSM-5 zeolite is increased, which can effectively provide acid sites and improve the reaction catalytic performance; (3) The preparation method is simple, low-cost, and recyclable, and has good application prospects in the field of furfural aqueous hydrogenation. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The diagram is a mechanism diagram of preparing γ-valerolactone by catalytic hydrogenation of furfural according to the present invention;

[0021] Figure 2 The diagram is a reaction mechanism diagram of the catalytic hydrogenation of furfural to prepare γ-valerolactone on catalysts of different configurations according to the present invention. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is further described below in conjunction with embodiments.

[0023] Example 1

[0024] The dual-configuration catalyst for furfural aqueous phase hydrogenation reaction of the present invention comprises a ZSM-5 zeolite molecular sieve as a carrier, and a metal M is nickel, wherein the ZSM-5 zeolite molecular sieve accounts for 61.4wt%, the Ni distributed inside the zeolite molecular sieve carrier accounts for 19.3%, and the Ni loaded on the surface of the zeolite molecular sieve carrier accounts for 19.3%. The preparation method of the catalyst comprises the following steps:

[0025] (1) Mix 20 mL of distilled water and 0.002 g of NaAlO 2 , 7.7 mL TPAOH, and 6.5 mL tetraethyl silicate to form a mixed solution, which was stirred at room temperature and 300 rpm for 6 h;

[0026] (2) 0.65 g of nickel nitrate hexahydrate and 1.6 g of PVP were added to the ZSM-5 precursor solution obtained in step (1), stirred at room temperature and 400 rpm for 15 min to mix evenly, and then transferred to a hydrothermal reactor for reaction at 80° C. for 36 h. After the reaction was completed, it was naturally cooled to room temperature, the reaction solution was taken out and centrifuged at 5000 rpm for 5 min, and then washed three times with deionized water. The product obtained by centrifugation was placed in a drying oven and dried at 60° C. for 15 h to obtain a Ni@ZSM-5 composite material;

[0027] (3) 0.65 g of nickel nitrate hexahydrate was added to a mixed solution of 6 mL of ammonia water (35 wt%) and 20 mL of deionized water, and stirred at room temperature and 400 rpm for 15 min to obtain a nickel complex ammonia solution [Ni(NH 3 ) 4 ] 2+ , the system pH is 12; the Ni@ZSM-5 composite material [Ni(NH 3 ) 4 ] 2+ The solutions were mixed, stirred at 400 rpm for 15 min at room temperature, and then placed in a hydrothermal reactor for reaction at 80°C for 24 h. After the reaction was completed, it was naturally cooled to room temperature, and the reaction solution was centrifuged at 5000 rpm for 5 min. Then, it was washed three times with deionized water, and the product obtained by centrifugation was placed in a drying oven and dried at 60°C for 15 h to obtain a dual-configuration composite material with layered nickel silicate in situ grown on the Ni@ZSM-5 surface.

[0028] (4) The product obtained in step (3) was placed in a muffle furnace and calcined at 400°C for 10 h under the influence of hydrogen (20 mL min -1 ) atmosphere and reduced at 300 °C for 5 h to obtain the furfural aqueous phase hydrogenation conversion dual-configuration catalyst Ni / Ni@ZSM-5.

[0029] The furfural aqueous phase hydrogenation conversion dual-configuration catalyst Ni / Ni@ZSM-5 prepared in this example was used for the selective hydrogenation of furfural to prepare γ-valerolactone. The specific reaction conditions and activity test results are as follows:

[0030] The furfural aqueous phase hydrogenation conversion dual-configuration catalyst was placed in a 250mL high-pressure reactor to evaluate the catalytic hydrogenation activity of furfural. The reaction system was 0.15g of catalyst, 1mL of furfural and 30mL of deionized water. The reaction was carried out for 8h at 80°C, 3.0MPa of hydrogen pressure and 800rpm stirring speed. After the reaction, the reaction mixture was centrifuged, the reaction liquid was taken, and the generated product was detected by gas chromatography. The furfural conversion rate was measured to be 92.5%, and the γ-valerolactone selectivity was 96.8%.

[0031] Example 2

[0032] The dual-configuration catalyst for furfural aqueous phase hydrogenation reaction of the present invention comprises a ZSM-5 zeolite molecular sieve as a carrier, and a metal M is nickel, wherein the ZSM-5 zeolite molecular sieve accounts for 67.2wt%, the Ni distributed inside the zeolite molecular sieve carrier accounts for 16.4%, and the Ni loaded on the surface of the zeolite molecular sieve carrier accounts for 16.4%. The preparation method of the catalyst comprises the following steps:

[0033] (1) Mix 17 mL of distilled water and 0.006 g of NaAlO 2 , 8.2 mL TPAOH, and 7 mL tetraethyl silicate to form a mixed solution, which was stirred at room temperature and 400 rpm for 4 h;

[0034] (2) 0.55 g of cobalt nitrate hexahydrate and 2.0 g of PVP were added to the ZSM-5 precursor solution obtained in step (1), stirred at room temperature and 500 rpm for 30 min to mix evenly, and then transferred to a hydrothermal reactor for reaction at 120° C. for 28 h. After the reaction was completed, it was naturally cooled to room temperature, the reaction solution was taken out and centrifuged at 6000 rpm for 4 min, and then washed three times with deionized water. The product obtained by centrifugation was placed in a drying oven and dried at 80° C. for 12 h to obtain a Ni@ZSM-5 composite material;

[0035] (3) 0.55 g of cobalt nitrate hexahydrate was added to a mixed solution of 7 mL of ammonia water (28 wt%) and 25 mL of deionized water, and stirred at room temperature and 500 rpm for 30 min to obtain a nickel complex ammonia solution [Ni(NH 3 ) 4 ] 2+ , the system pH is 10; the Ni@ZSM-5 composite material obtained in step (2) and the obtained [Ni(NH 3 ) 4 ] 2+ The solutions were mixed, stirred at 500 rpm for 30 min at room temperature, and then placed in a hydrothermal reactor for reaction at 120°C for 20 h. After the reaction was completed, the mixture was naturally cooled to room temperature, and the reaction solution was centrifuged at 6000 rpm for 4 min. The mixture was then washed three times with deionized water, and the product obtained by centrifugation was placed in a drying oven and dried at 80°C for 12 h to obtain a dual-configuration composite material with layered nickel silicate in situ grown on the surface of Ni@ZSM-5.

[0036] (4) The product obtained in step (3) was placed in a muffle furnace and calcined at 500°C for 7 h under the influence of hydrogen (30 mL min -1 ) atmosphere and reduced at 400 °C for 4 h to obtain the furfural aqueous phase hydrogenation conversion dual-configuration catalyst Ni / Ni@ZSM-5.

[0037] The furfural aqueous phase hydrogenation conversion dual-configuration catalyst Ni / Ni@ZSM-5 prepared in this example was used for the selective hydrogenation of furfural to prepare γ-valerolactone. The specific reaction conditions and activity test results are as follows:

[0038] The furfural aqueous phase hydrogenation conversion dual-configuration catalyst was placed in a 250mL high-pressure reactor to evaluate the catalytic hydrogenation activity of furfural. The reaction system was 0.45g of catalyst, 2mL of furfural and 50mL of deionized water. The reaction was carried out for 6 hours at 120°C, 2.0MPa of hydrogen pressure and 900rpm stirring speed. After the reaction, the reaction mixture was centrifuged, the reaction liquid was taken, and the generated product was detected by gas chromatography. The furfural conversion rate was measured to be 90.1%, and the γ-valerolactone selectivity was 95.4%.

[0039] Example 3

[0040] The dual-configuration catalyst for furfural aqueous phase hydrogenation reaction of the present invention comprises a ZSM-5 zeolite molecular sieve as a carrier, and a metal M is nickel, wherein the ZSM-5 zeolite molecular sieve accounts for 75.4wt%, the Ni distributed inside the zeolite molecular sieve carrier accounts for 12.3%, and the Ni loaded on the surface of the zeolite molecular sieve carrier accounts for 12.3%. The preparation method of the catalyst comprises the following steps:

[0041] (1) Mix 15 mL of distilled water and 0.012 g of NaAlO 2 , 8.7 mL TPAOH, and 8 mL tetraethyl silicate to form a mixed solution, which was stirred at room temperature and 500 rpm for 3 h;

[0042] (2) 0.45 g of copper nitrate trihydrate and 2.4 g of PVP were added to the ZSM-5 precursor solution obtained in step (1), stirred at room temperature and 600 rpm for 15 min to mix evenly, and then transferred to a hydrothermal reactor for reaction at 180° C. for 10 h. After the reaction was completed, it was naturally cooled to room temperature, the reaction solution was taken out and centrifuged at 7000 rpm for 2 min, and then washed three times with deionized water. The product obtained by centrifugation was placed in a drying oven and dried at 110° C. for 8 h to obtain a Ni@ZSM-5 composite material;

[0043] (3) 0.45 g of copper nitrate trihydrate was added to a mixed solution of 8 mL of ammonia water (15 wt%) and 30 mL of deionized water, and stirred at room temperature and 600 rpm for 15 min to obtain a nickel complex ammonia solution [Ni(NH 3 ) 4 ] 2+ , the system pH is 9; the Ni@ZSM-5 composite material obtained in step (2) and the obtained [Ni(NH 3 ) 4 ]2+ The solutions were mixed, stirred at 600 rpm for 15 min at room temperature, and then placed in a hydrothermal reactor for reaction at 180°C for 14 h. After the reaction was completed, the mixture was naturally cooled to room temperature, and the reaction solution was centrifuged at 7000 rpm for 2 min. The mixture was then washed three times with deionized water, and the product obtained by centrifugation was placed in a drying oven and dried at 110°C for 8 h to obtain a dual-configuration composite material with layered nickel silicate in situ grown on the surface of Ni@ZSM-5.

[0044] (4) The product obtained in step (3) was placed in a muffle furnace and calcined at 600°C for 4 h under hydrogen (40 mL min -1 ) atmosphere and reduced at 600 °C for 2 h to obtain the furfural aqueous phase hydrogenation conversion dual-configuration catalyst Ni / Ni@ZSM-5.

[0045] The furfural aqueous phase hydrogenation conversion dual-configuration catalyst Ni / Ni@ZSM-5 prepared in this example was used for the selective hydrogenation of furfural to prepare γ-valerolactone. The specific reaction conditions and activity test results are as follows:

[0046] The furfural aqueous phase hydrogenation conversion dual-configuration catalyst was placed in a 250mL high-pressure reactor to evaluate the catalytic hydrogenation activity of furfural. The reaction system was 0.3g catalyst, 4mL furfural and 40mL deionized water. The reaction was carried out for 3h at 150°C, 2.0MPa hydrogen pressure and 1000rpm stirring speed. After the reaction, the reaction mixture was centrifuged, the reaction liquid was taken, and the generated product was detected by gas chromatography. The furfural conversion rate was measured to be 98.2%, and the γ-valerolactone selectivity was 88.6%.

[0047] Example 4

[0048] The dual-configuration catalyst for furfural aqueous phase hydrogenation reaction of the present invention comprises a ZSM-5 zeolite molecular sieve as a carrier, and a metal M is nickel, wherein the ZSM-5 zeolite molecular sieve accounts for 82.2wt%, the Ni distributed inside the zeolite molecular sieve carrier accounts for 8.9%, and the Ni loaded on the surface of the zeolite molecular sieve carrier accounts for 8.9%. The preparation method of the catalyst comprises the following steps:

[0049] (1) Mix 10 mL of distilled water and 0.02 g of NaAlO 2 , 9 mL TPAOH, and 9 mL tetraethyl silicate to form a mixed solution, which was stirred at room temperature and 600 rpm for 1 h;

[0050] (2) 0.35 g of ferric nitrate nonahydrate and 2.8 g of PVP were added to the ZSM-5 precursor solution obtained in step (1), stirred at room temperature and 700 rpm for 10 min to mix evenly, and then transferred to a hydrothermal reactor for reaction at 200 ° C for 5 h. After the reaction was completed, it was naturally cooled to room temperature, the reaction solution was taken out and centrifuged at 9000 rpm for 1 min, and then washed three times with deionized water. The product obtained by centrifugation was placed in a drying oven and dried at 120 ° C for 5 h to obtain a Ni@ZSM-5 composite material.

[0051] (3) 0.35 g of ferric nitrate nonahydrate was added to a mixed solution of 9 mL of ammonia water (8 wt%) and 35 mL of deionized water, and stirred at room temperature and 700 rpm for 10 min to obtain a nickel complex ammonia solution [Ni(NH 3 ) 4 ] 2+ , the system pH is 7; the Ni@ZSM-5 composite material obtained in step (2) and the obtained [Ni(NH 3 ) 4 ] 2+ The solutions were mixed, stirred at 700 rpm for 10 min at room temperature, and then placed in a hydrothermal reactor for reaction at 200 °C for 10 h. After the reaction was completed, it was naturally cooled to room temperature, and the reaction solution was centrifuged at 9000 rpm for 1 min. Then, it was washed three times with deionized water, and the product obtained by centrifugation was placed in a drying oven and dried at 120 °C for 5 h to obtain a dual-configuration composite material with layered nickel silicate in situ grown on the Ni@ZSM-5 surface.

[0052] (4) The product obtained in step (3) was placed in a muffle furnace and calcined at 700°C for 3 h under the influence of hydrogen (50 mL min -1 ) atmosphere and reduced at 700 °C for 1 h to obtain the furfural aqueous phase hydrogenation conversion dual-configuration catalyst Ni / Ni@ZSM-5.

[0053] The furfural aqueous phase hydrogenation conversion dual-configuration catalyst Ni / Ni@ZSM-5 prepared in this example was used for the selective hydrogenation of furfural to prepare γ-valerolactone. The specific reaction conditions and activity test results are as follows:

[0054] The furfural aqueous phase hydrogenation conversion dual-configuration catalyst was placed in a 250mL high-pressure reactor to evaluate the catalytic hydrogenation activity of furfural. The reaction system was 0.15g of catalyst, 1mL of furfural and 25mL of deionized water. The reaction was carried out at 180°C, 0.5MPa of hydrogen pressure and 1200rpm of stirring speed for 10h. After the reaction, the reaction mixture was centrifuged, the reaction liquid was taken, and the generated product was detected by gas chromatography. The furfural conversion rate was measured to be 90.6%, and the γ-valerolactone selectivity was 95.5%.

Claims

1. Application of a dual-configuration catalyst in the preparation of γ-valerolactone by aqueous phase hydrogenation of furfural, characterized in that: The carrier of the dual-configuration catalyst is a ZSM-5 zeolite molecular sieve, and the carrier zeolite molecular sieve includes two parts of metal M, one part of the metal M is uniformly dispersed inside the zeolite molecular sieve and wrapped by the zeolite molecular sieve, and the other part of the metal M is uniformly loaded on the surface of the zeolite molecular sieve; wherein the metal M is Ni, Cu, Fe or Co; The preparation method of the dual-configuration catalyst comprises the following steps: (1) Preparing a ZSM-5 precursor solution; (2) mixing the metal M salt, polyvinyl pyrrolidone and ZSM-5 precursor solution, stirring them evenly, and then performing a hydrothermal reaction to obtain a ZSM-5 zeolite molecular sieve coated with metal M M@ZSM-5 composite material; (3) Dissolve the metal M salt in the ammonia solution and stir evenly to form a metal M complex ammonia solution [M(NH3)4] 2+ , adding the M@ZSM-5 composite material obtained in step (2), stirring evenly, and performing a hydrothermal reaction to obtain a dual-configuration composite material with layered metal M silicate in situ grown on the surface of M@ZSM-5; (4) The product obtained in step (3) is subjected to high temperature roasting and reduction to obtain a furfural aqueous phase hydrogenation conversion dual-configuration catalyst M / M@ZSM-5.

2. The use according to claim 1, characterized in that: The content of the ZSM-5 zeolite molecular sieve is 60-80 wt %, the content of the metal M dispersed inside the zeolite molecular sieve is 1-20 wt %, and the content of the metal M loaded on the surface of the zeolite molecular sieve is 1-20 wt %.

3. The use according to claim 1, characterized in that: The ZSM-5 zeolite molecular sieve is subjected to Si removal treatment.

4. The use according to claim 1, characterized in that: In step (1), the ZSM-5 precursor solution is a mixture of TEOS:NaAlO2:TPAOH:H2O in a molar ratio of 1:(0.002-0.04):(0.015-0.3):(10-50).

5. The use according to claim 1, characterized in that: In step (2), the hydrothermal reaction conditions are 80-200° C. for 5-36 hours.

6. The use according to claim 1, characterized in that: In step (3), in the complex ammonia solution of the metal M, the [M(NH3)4] 2+ The content of is 0.05~2 wt%, the content of ammonia is 5~35 wt%, and the pH value of the metal complex ammonia solution is 9~12.

7. The use according to claim 1, characterized in that: In step (3), the hydrothermal reaction conditions are 80-200° C. for 10-24 h.

8. The use according to claim 1, characterized in that: In step (4), the calcination condition is calcination at 400-700°C for 3-10 h; the reduction condition is reduction at 300-700°C for 1-5 h, and the reducing atmosphere is H2 or H2 / N2 mixed gas.

9. The use according to claim 1, characterized in that: The metal M salt is metal M nitrate.

Citation Information

Patent Citations

  • Catalyst for catalyzing furfural hydrogenation to prepare furfuryl alcohol, preparation method and application thereof

    CN111111744A

  • Polycyclic aromatic hydrocarbon hydrogenation catalyst and preparation method thereof

    CN112536040A